PEMANFAATAN MEDIA DALAM PROSES PEMBELAJARAN IPS TERPADU DI SEKOLAH MENENGAH PERTAMA DI KECAMATAN PARINGIN DAN PARINGIN SELATAN - Aji Hermawan; Parida Angriani; Karunia Puji Hastuti (Universitas Lambung Mangkurat, 2015)
This study, entitled Use of Media Integrated Social Learning Processes in Secondary School in District Paringin and South Paringin, collated by Aji Hermawan. Supervisor I: Angriani Parida, M Ed and lecturers II: The Gift of Praise Hastuti, M.Pd. The purpose of this research is in knowing the benefits of media use in the learning process of social studies in junior high school in the district Integrated Paringin and South Paringin. The population in this study were junior high school social studies teacher in the district Integrated Paringin and South Paringin amounted to 7 teachers. The primary data obtained through observation, questionnaire or koesioner, and interviews. Secondary data was obtained from the District Education Office Balangan, Planning Balangan, junior in the district and Paringin Paringin South, the research method used in this study is a quantitative method. The results showed that, the benefits of the media in the process of learning social studies in junior districts Integrated Paringin and South Paringin is very useful in the learning process at school Integrated Social Science.Keywords: Media, Teacher, IPS Integrated